A 1960MPa grade hot-rolled wire rod for bridge cables and a manufacturing method thereof

Through the design of C-Si-Mn-Cr composition and online molten salt strong isothermal technology, the problems of mesh carbides and abnormal tissue in hot-rolled strips are solved, the strength and high plasticity matching is achieved, the risk of unqualified wire making and torsion is reduced, and the demand for 1960MPa-level bridge cables is met.

CN119144802BActive Publication Date: 2025-04-29JIANGSU YONGGANG GROUP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411650083.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-29
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

In the process of increasing strength and controlling costs, the existing hot-rolled strips for 1960MPa-level bridge cables have the formation of mesh carbides and abnormal tissues, which affects the uniformity and plasticity of the tissue, resulting in poor wire making and torsional performance.

Method used

The C-Si-Mn-Cr supereutectic component design is adopted, combined with the online molten salt strong isothermal technology, through the molten salt treatment of the front and rear sections, the control strip quickly enters the soxunite phase region from the high-temperature austenite state, and undergoes short-term tempering to inhibit the formation of reticular carbides and promote the transformation of soxunite and pearlite.

Benefits of technology

The strength and high plasticity of hot-rolled strips are achieved, which reduces the risk of wire breakage and twisting failure, improves the structural uniformity and mechanical performance stability, and meets the strength level requirements of 1960MPa-level bridge cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144802B_ABST
    Figure CN119144802B_ABST
Patent Text Reader

Abstract

The invention relates to a hot-rolled wire rod for 1960MPa-grade bridge cables and a manufacturing method thereof. After rolling and spinning into a wire rod using a C-Si-Mn-Cr hypereutectoid component, the wire rod is subjected to an online molten salt strong isothermal treatment, so that the wire rod first passes through a front-stage molten salt and is cooled at a cooling rate of ≥36°C / s, enters a sorbite phase region from an austenite state, promotes the transformation of part of austenite into sorbite, then undergoes a rear-stage molten salt heating isothermal treatment, promotes pearlite phase transformation and isothermal tempering, and finally undergoes roller slow cooling to obtain a microstructure including a mixed structure mainly composed of tempered sorbite and tempered pearlite, and the rest being ferrite and quasi-spheroidized carbide. The component system can be simplified, the wire rod structure can be uniformly regulated, and the tensile strength can reach 1360-1410MPa and the cross-sectional shrinkage can reach 45%-50%, which is conducive to meeting the strength grade requirement of 1960MPa-grade bridge cables and reduces the risks of wire breakage and torsion failure during wire making.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hot-rolled wire rods, and in particular relates to a 1960MPa-grade hot-rolled wire rod for bridge cables and a manufacturing method thereof. Background Art

[0002] With the continuous improvement of metallurgical quality and wire drawing technology, bridge cables have gradually been upgraded from 1660MPa to 1960MPa. For example, Yanji Yangtze River Bridge, Libu Yangtze River Highway-Railway Bridge, Zhoushan Port Liuheng Bridge and other large-span bridges all use high-strength 1960MPa bridge cables. The higher the strength level of the bridge cable, the higher the strength of the required parent material. At the same time, the parent material wire rod reduction rate of bridge cables in the wire making process is as high as 90%, so extremely stringent requirements are placed on the uniformity of the structure and cold processing performance of the parent material wire rod. At present, the hot-rolled wire rods for 1960MPa bridge cables are mainly made by increasing the content of C elements and hardenability elements, combined with the Stelmor air-cooled wire after hot rolling to form a fine pearlite structure. The hot-rolled wire rods with lower manufacturing costs, higher strength grades, and better wire making and torsion performance still have the following technical difficulties:

[0003] 1. In order to improve the strength of wire rod and control the cost, the C content in the composition is relatively large, but hypereutectoid steel will aggravate the segregation during the solidification process of the alloy. Limited by the maximum cooling capacity of the air-cooling line, the time for the secondary cementite on the air-cooling line is longer, and it is easier to precipitate network carbides along the grain boundaries, destroying the continuity of the organization and seriously affecting the plasticity of the wire rod, thereby causing fractures during deep drawing or torsion. Reducing the carbon content and increasing the air volume of the air-cooling line fan have limited improvement on the network carbides and will also bring about a certain loss of strength. It is necessary to increase the content of alloy strengthening elements, resulting in increased material costs.

[0004] 2. Alloy strengthening and microstructure refinement are the main means to improve the strength of wire rod. For this reason, hardenability elements such as Mn, Cr, B, Mo, etc. will be further added to the high carbon steel wire rod of bridge cable, or the element addition will be increased, so as to reduce the phase transition temperature and delay the troostite phase transition time, so that finer pearlite lamellar spacing can be obtained during the phase transition to improve the matrix strength. However, the increase of hardenability elements will also aggravate the segregation of alloy elements. In order to minimize the influence of network carbides and promote the finer spacing of pearlite lamellars, the air cooling line after spinning will increase the fan air volume. The increase in air volume also increases the uncontrollability of wind temperature, wind speed, etc. The temperature difference between the windward side and the leeward side of the wire rod, the overlap and non-overlap, and the edge to the core of the same cross section will be further increased. Affected by hardenability elements and segregation, austenite in some overcooled positions is more likely to be transformed into hard and brittle phase structures such as bainite and martensite, which are unfavorable to the drawing performance, affecting the uniformity of the organization, increasing the brittleness and mechanical property fluctuations of the wire rod, and bringing the risk of wire breakage and torsion failure.

[0005] For example, patent CN109554631B discloses a low alloy steel and a high-strength and high-plasticity wire rod for steel wire processing made therefrom, which is designed with C-Si-Mn-Cr-Ni-Cu-Al or also contains Mo or B components, combined with the Stelmor air cooling line to first cool quickly and then slowly, and then use austenite heating and isothermal treatment for offline lead bath or salt bath treatment to improve strength and plasticity and mechanical fluctuations, but offline processing will further increase the process, energy consumption, production time, etc., bringing cost pressure to the manufacture of wire rods and bridge cables.

[0006] 3. In order to improve the strength of wire rod, the current high carbon steel wire rod for bridge cables mainly improves the matrix strength by maximizing the content of fine pearlite, i.e. troostite, in the wire rod structure. However, on the one hand, even if the fan air volume is reduced, due to the minimum cooling rate and online time of the Stelmor air cooling line, as well as the influence of the diffusion activity of carbon after the addition of alloying elements, the organization incubation time of the wire rod in the phase transformation temperature range is short, which limits the improvement of the troostitization rate. The proportion of soft phase ferrite in the structure is high, which will lose the strengthening effect. On the other hand, the addition of hardenability elements increases the difficulty of improving plasticity. The completion of the wire rod phase transformation in a short time will cause the wire rod to have a high residual stress inside. At the same time, after the wire rod phase transformation is incubated, it is in a low temperature state during the continuous cooling process, which makes the formed troostite structure have a large dislocation density and the wire rod has insufficient plasticity. In the subsequent drawing process, the drawing hardening is obvious, which is easy to cause wire breakage or torsion failure during deep drawing. Summary of the invention

[0007] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a 1960MPa grade hot-rolled wire rod for bridge cables and a manufacturing method thereof, which can simplify the component system, regulate the uniformity of the wire rod structure, and achieve matching of strength and high plasticity, which is conducive to meeting the strength grade requirements of 1960MPa grade bridge cables, while reducing the risks of wire breakage and torsion failure during wire making.

[0008] The technical solution adopted by the present invention to solve its technical problem is:

[0009] A method for manufacturing a 1960MPa grade hot-rolled wire rod for bridge cables, the manufacturing method comprising:

[0010] The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.86% to 0.90%, Si: 0.48% to 0.65%, Mn: 0.50% to 0.70%, Cr: 0.35% to 0.45%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is spun into wire rod at a spinning temperature of ≥925°C. After online molten salt strong isothermal treatment, the wire rod first passes through the front section of molten salt and is cooled at a cooling rate of ≥36℃ / s, entering the sorbite phase region from the austenite state, promoting the transformation of part of the austenite to the sorbite, and then passes through the rear section of molten salt heating isothermal treatment to promote the pearlite phase transformation and isothermal tempering, and finally passes through roller slow cooling to produce a hot rolled wire rod with a microstructure mainly composed of tempered sorbite and tempered pearlite, and the rest is a mixed structure composed of ferrite and quasi-spheroidized carbide.

[0011] The design basis of the chemical composition and mass percentage of the above hot rolled wire rod includes:

[0012] (1) Carbon: As an effective carbide strengthening element and austenite forming element, C is cheaper than other alloying elements. It can form more cementite lamellae through solid solution strengthening and precipitation strengthening, thereby improving the strength of the wire rod. However, as the carbon content in hypereutectoid steel increases, the central segregation and decarburization tendency of the steel billet will increase, and the control difficulty of abnormal structures such as network carbides, bainite and martensite will increase, affecting the drawing and torsion properties. Therefore, in order to take into account the high strength requirements of 1960MPa grade bridge cables and reduce the difficulty of controlling abnormal structures, it is more conducive to refining the troostite and pearlite lamellae during online molten salt strong isothermal treatment and improving the strengthening effect of carbon elements. The mass percentage of C is controlled to be 0.86%~0.90%.

[0013] (2) Silicon: The Si element is often used as a deoxidizer during the smelting process. It is dissolved in the ferrite phase to improve the material strength. At the same time, it can inhibit the coarsening of cementite, which is beneficial to obtaining a finer troostite structure in the previous molten salt treatment. It can accelerate the diffusion rate of carbon, which is beneficial to promoting the transformation of carbides to spheroidization and rapid tempering in the subsequent molten salt treatment. After the wire rod is drawn into steel wire, it can reduce the strength loss in the subsequent hot-dip galvanizing process. However, too high a silicon content will make the steel easier to decarburize when heated at high temperature and reduce the toughness of pearlite. Therefore, the Si content is appropriately increased, and the mass percentage of Si is controlled to be 0.48%~0.65%.

[0014] (3) Manganese: Mn can be added as a deoxidizer in the steelmaking process, mainly playing a role in solid solution strengthening, while increasing the hardenability of the wire rod and reducing the phase transformation temperature, which is beneficial to the rapid nucleation of the troostite structure with fine lamellar spacing during the front-end molten salt treatment, and can improve the matrix strength. However, when the Mn content is too high, it will increase the tendency of grain coarsening and component segregation, and it will be easier to form low-temperature brittle structure, increasing the difficulty of abnormal structure control, and at the same time reduce the diffusion activity of carbon, which is not conducive to promoting the rapid short-term tempering softening of troostite and pearlite during the back-end molten salt treatment, thereby reducing the plasticity of the wire rod. Therefore, in order to take into account the high strength and plasticity of the hot-rolled wire rod, the Mn content is appropriately reduced, and the mass percentage of Mn is controlled to be 0.50%~0.70%.

[0015] (4) Chromium: Cr is a medium-strong carbide-forming element in high carbon steel. It can improve the stability of austenite and the hardenability of wire rod, reduce the interlamellar spacing between troostite and pearlite, increase the matrix strength, and improve the drawing processing performance, so as to facilitate large drawing deformation and reduce the strength loss during the subsequent hot-dip galvanizing process of steel wire. However, too high Cr content will aggravate component segregation, increase the risk of abnormal tissue precipitation, reduce the activity of carbon in steel, and be unfavorable for short-term tempering softening during the subsequent molten salt treatment, resulting in increased difficulty in improving plasticity. Therefore, the Cr content is appropriately increased, and the mass percentage of Cr is controlled to be 0.35%~0.45%.

[0016] (5) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.

[0017] The hot-rolled wire rod adopts the C-Si-Mn-Cr hypereutectoid composition design without Ni, B, Mo and other elements, which can simplify the composition system, reduce the material cost, and take into account the hardenability of the wire rod, so as to inhibit the coarsening of cementite, refine the sorbite and pearlite lamellae, and promote the short-time tempering of the organization. On this basis, a higher spinning temperature is selected to austenitize the wire rod organization, avoid the formation of network carbides due to too low temperature in the spinning stage, and provide favorable conditions for the formation of a large temperature gradient to inhibit the precipitation of network carbides and promote the nucleation of sorbite. After the wire rod is spun, it is directly subjected to online molten salt strong isothermal treatment:

[0018] 1. Compared with the Stelmor air-cooled line, which is unable to control the precipitation of network carbides and cause cementite coarsening due to its limited maximum cooling capacity, the above-mentioned manufacturing method can utilize the high heat exchange capacity of molten salt, combined with the relatively low temperature of the sorbite phase region, to promote the rapid cooling of the wire rod from the spinning temperature. On the one hand, it can quickly skip the 700~800℃ secondary cementite precipitation temperature range, thereby effectively inhibiting the network carbides precipitated along the grain boundaries, and avoiding its destruction of the uniformity of the organization and the plasticity of the wire rod. On the other hand, it can enable the wire rod to quickly enter the sorbite phase region from the high-temperature austenite state, forming a large degree of supercooling, and promoting the rapid transformation of part of the austenite structure to the sorbite structure with finer interlamellar spacing, so as to improve the matrix strength and drawing performance, have appropriate drawing hardening processing performance, and make it easier for the wire rod to reach the corresponding strength grade after deep drawing, and provide favorable conditions for the short-term tempering of the subsequent molten salt treatment.

[0019] 2. Compared with the influence of segregation and hardenability, it is difficult to control abnormal organization in the Stelmore air-cooled line due to the uncontrollable cooling rate. When the wire rod passes through the molten salt, the molten salt can cover the surface of the wire rod for rapid and uniform heat exchange, and there is no temperature difference between the windward side and the leeward side. The temperature difference from the upper edge to the core of the wire rod section can be reduced. Therefore, on the one hand, after the wire rod enters the troostite phase region, it can form a structure dominated by troostite with fine interlamellar spacing, improve the uniformity of troostite distribution, and avoid overcooling of the wire rod to form bainite or martensite hardness that is unfavorable to drawing and plasticity. Brittle structure. On the other hand, when the wire rod is treated with molten salt in the latter stage, the temperature of the wire rod can be consistent with that of the molten salt, which can prolong the phase transformation incubation time and promote the rapid transformation of high-temperature austenite that has not been transformed when passing through the former molten salt into pearlite structure. The full transformation of the austenite structure and the higher treatment temperature further avoid the formation of abnormal structure and effectively improve the uniformity of the structure. Compared with the offline salt bath treatment, it no longer requires air cooling, repeated winding and unwinding, re-austenitizing and heating, which is beneficial to improving production capacity and efficiency and reducing production costs.

[0020] 3. Compared with the existing Stelmore air-cooling line, which has limited minimum cooling capacity and continuous cooling control, making the wire rod structure difficult to control and insufficient in strength and plasticity, the above-mentioned manufacturing method is different from the traditional continuous cooling treatment. Instead, it is a isothermal treatment of molten salt in the back stage after the front stage molten salt treatment. On the one hand, by extending the treatment time of the peak precipitation temperature, it can promote the full transformation of austenite structure to troostite and pearlite structure, reduce the proportion of ferrite, improve the strength of the matrix, and make the proportion of troostite and pearlite more controllable. The pearlite structure with higher strength than ferrite and better plasticity than troostite can be used to appropriately regulate the plasticity of the matrix. On the other hand, the post-treatment temperature of the back stage molten salt heating is higher High, the temperature of the wire rod is consistent with that of the molten salt, which can maintain a high-temperature isothermal state for a longer time, provide more thermal power for the softening and tempering of the organization, promote the newly formed troostite and pearlite organizations to reduce the organization stress and dislocation density, promote the rapid transformation of carbides to spheroidized organizations, perform short-time tempering, and improve the strength-plasticity matching of the wire rod, which is beneficial to efficient production and avoiding the polymerization and growth of Cr precipitation phase under long-term high temperature; at the same time, due to the relatively high temperature of the molten salt in the latter stage, the cooling rate of the wire rod can be further reduced after the wire rod is slowly cooled by the roller, and the tempering effect of the later stage of the molten salt treatment in the latter stage can be continued, which promotes further toughening of the organization, thereby realizing microstructure regulation and high-strength-plasticity matching of the wire rod.

[0021] Controlling the soaking temperature and treatment time of the heating furnace before rolling can promote uniform diffusion of alloy components and reduce the influence of segregation, while further controlling the air-fuel ratio to avoid decarburization on the surface of the steel billet and affect the wire rod structure. In a preferred embodiment, before rolling, the soaking temperature of the heating furnace is controlled to be 1120~1160℃, the time in the furnace is 130~190min, and the air-fuel ratio is ≤0.52.

[0022] Before rolling, a higher descaling pressure is selected after heating in a heating furnace, and high-pressure water is used to remove the oxide scale on the surface of the billet, which can prevent the oxide scale from being rolled into the wire and affecting the surface quality of the wire rod. In a preferred embodiment, before rolling, the descaling pressure is controlled to be ≥18MPa.

[0023] Since the spinning temperature is relatively high, appropriate rolling temperature and reduction are selected to avoid decarburization caused by excessively high temperature, avoid excessively low temperature causing large deformation resistance of the steel billet and increasing the load on the rolling mill, promote dynamic recrystallization during the final rolling process, refine the grains, and strengthen the matrix. In a preferred embodiment, during the rolling, the initial rolling temperature is controlled to be 1050~1090℃, the final rolling temperature is 940~980℃, and the final rolling reduction is 28%~33%.

[0024] Since the spinning and rolling temperatures are high, the deformation resistance of the steel billet decreases, and a faster rolling speed can improve the rolling efficiency and production rhythm. In a preferred embodiment, during the rolling, the rolling speed is controlled to be ≥32m / s.

[0025] The molten salt temperature of the front stage molten salt is in the troostite phase region. The lower the molten salt temperature and the longer the treatment time, the more the high-temperature austenite phase troostite structure is transformed, the finer the troostite lamellar structure is, and the matrix strength increases. However, if the molten salt temperature is too low, it is not conducive to controlling the abnormal bainite structure. At the same time, increasing the temperature gradient will increase the molten salt circulation volume and energy consumption. If the treatment time is too long, more troostite nuclei will form, which will affect the transformation of pearlite structure and reduce the matrix plasticity. On the contrary, if the molten salt temperature is higher and the treatment time is shorter, it will be not conducive to the nucleation of troostite dominated by fine lamellar spacing, which will cause the untransformed high The warm austenite structure increases, the pearlite transformation increases, and the matrix strength decreases. However, if the molten salt temperature is too high and the treatment time is too short, the sorbite transformation will be too little, which will affect the wire rod strength and drawing hardening performance. If the molten salt temperature is too high, the wire rod cooling rate will be reduced and the network carbide control will be affected. Therefore, the molten salt temperature and treatment time of the front-stage molten salt can be further controlled to promote the transformation of part of the high-temperature austenite to the sorbite structure, so as to make organizational preparations for the rear-stage molten salt treatment. In a preferred embodiment, the molten salt temperature of the front-stage molten salt is 545~575℃, and the treatment time is 15~30s.

[0026] Since the wire rod is cooled from a higher spinning temperature to the troostite phase temperature with a large temperature difference, a higher molten salt circulation rate is selected to reduce the temperature rise of the molten salt, which can further control the processing accuracy of the front-stage molten salt and improve the uniformity of the structure. In a preferred embodiment, the molten salt circulation rate of the front-stage molten salt is 550~650t / h, and the temperature rise of the molten salt is ≤8°C.

[0027] The molten salt temperature of the rear-stage molten salt is appropriately higher than that of the front-stage molten salt. The higher the molten salt temperature and the longer the treatment time, the more the untransformed austenite structure is transformed into the pearlite structure. At the same time, more thermal power can be provided to promote the short-time isothermal tempering of the troostite and pearlite structures, promote the spheroidization of carbides, and improve the plasticity of the matrix. However, if the molten salt temperature is too high and the treatment time is too long, there is a risk of softening too quickly, losing the strength of the wire rod due to excessive softening, and losing the strong and plastic properties due to the aggregation and growth of carbides such as Cr. At the same time, it is not conducive to efficient production and reducing production energy consumption. On the contrary, the lower the molten salt temperature, the more conducive it is to the refinement of the pearlite lamellae. Spacing, improve matrix strength and drawing performance, the shorter the processing time, the lower the tempering softening effect, the lower the plasticity of the wire rod, but if the molten salt temperature is too low and the processing time is too short, it is difficult to provide more thermal power for tissue softening and carbide spheroidization, and insufficient plasticity of the wire rod will increase the risk of drawing and torsional fracture. Therefore, the molten salt temperature and processing time of the rear-stage molten salt can be further controlled to promote pearlite structure nucleation and short-time tempering, and regulate the matching of wire rod structure and strength and plasticity. In a preferred embodiment, the molten salt temperature of the rear-stage molten salt is 558~595℃, and the processing time is 50~150s.

[0028] Since the temperature rise of the molten salt in the rear stage is smaller than that in the front stage, appropriately reducing the molten salt circulation volume can accurately control the temperature, promote the uniform transformation of untransformed austenite to pearlite structure, and reduce production energy consumption. In a preferred embodiment, the molten salt circulation volume of the rear stage molten salt is 300~450t / h, and the molten salt temperature rise is ≤3°C.

[0029] In a preferred embodiment, the roller slow cooling controls the wire rod to be cooled to below 300°C at a slow cooling rate of 0.5~0.9°C / s for coiling, which can avoid the loss of wire rod plasticity caused by too high a slow cooling rate, avoid the loss of wire rod strength and extended online time caused by too low a slow cooling rate, improve the softening effect of the wire rod, and promote the rapid offline of the wire rod.

[0030] In a preferred embodiment, the roller slow cooling adopts an open insulation cover, and the wire rod is conveyed into the insulation cover by rollers. The wire rod's own waste heat can be used to control the slow cooling speed, so as to increase the roller conveying speed and reduce the online time of the wire rod.

[0031] A 1960MPa grade hot-rolled wire rod for bridge cables, the hot-rolled wire rod is manufactured by any one of the above-mentioned methods for manufacturing the 1960MPa grade hot-rolled wire rod for bridge cables.

[0032] The hot-rolled wire rod adopts a hypereutectoid composition design, does not contain expensive alloy components such as Ni, B, and Mo, and has a lower material cost. At the same time, it is different from the traditional wire rod structure for bridge cables with a high sorbitization rate. The microstructure of the hot-rolled wire rod is mainly tempered sorbite and tempered pearlite, containing a small amount of ferrite and quasi-spheroidized carbide. The sorbite has a finer interlamellar spacing than the pearlite, and has higher strength and drawing hardening ability, which is beneficial to improving the strength grade of the steel wire during deep drawing. After the sorbite is transformed into the tempered sorbite after a short tempering, the dislocation density decreases, and the plastic toughness is better, which is beneficial to reduce the plastic loss and fracture risk during deep drawing. Pearlite has higher strength and higher plasticity than ferrite, which can improve the plasticity of the matrix. Pearlite is transformed into tempered pearlite after short-time tempering, which can further reduce the organizational stress and dislocation density. Combined with tempered troostite, the proportion of ferrite in the organization is reduced, the matrix strength is comprehensively improved, and the strengthening effect of C and alloy elements is fully exerted to make up for the strength loss caused by not adding precious alloy components such as Ni, B, and Mo. At the same time, the carbide is transformed into a spheroidized organization. After becoming a quasi-spheroidized carbide, it can be evenly distributed on the plastic matrix. The organization has better plasticity and toughness after tempering, does not contain abnormal organizations such as bainite and martensite, and has better organizational uniformity. It can effectively reduce the crack tendency during deep drawing and torsion, and is suitable for the manufacture of 1960MPa-level bridge cables, which is beneficial to improving the yield rate and reducing the manufacturing cost of bridge cables.

[0033] In a preferred embodiment, the volume percentage of the tempered bainite is 33%~40%, and the volume percentage of the tempered pearlite is 53%~62%. The higher the proportion of tempered bainite, the higher the strength of the wire rod, the lower the plasticity, and the enhanced drawing hardening ability. The higher the proportion of tempered pearlite, the lower the strength of the wire rod, the higher the plasticity, and the lower the tendency of drawing cracks. Therefore, the proportion of tempered bainite and tempered pearlite can be further controlled to adjust the strength and plasticity matching of the hot-rolled wire rod.

[0034] The finer the interlamellar spacing of the tempered troostite, the higher the matrix strength, which can reduce the difficulty of tempering, but the difficulty of controlling abnormal tissue increases. In a preferred embodiment, the interlamellar spacing of the tempered troostite is 80-135 nm.

[0035] The finer the lamellar spacing of the tempered pearlite, the better the drawing performance, but the molten salt temperature of the subsequent molten salt decreases, which is not conducive to rapid softening and causes plasticity loss of the wire rod. In a preferred embodiment, the lamellar spacing of the tempered pearlite is 155~180nm.

[0036] In a preferred embodiment, the network carbide level of the hot-rolled wire rod is level 0, which can enhance the strengthening effect of the carbon element and improve the overall strength and plasticity of the wire rod.

[0037] Since the network carbides and low-temperature abnormal tissues of the wire rod are effectively controlled, the tempered troostite and tempered pearlite are evenly distributed, the tissue uniformity is better, and the fluctuation of mechanical properties is correspondingly reduced, the risks of wire breakage and torsion failure in wire making can be effectively reduced. In a preferred embodiment, the same-circle difference of the mechanical properties of the hot-rolled wire rod is ≤45MPa.

[0038] In a preferred embodiment, the diameter of the hot-rolled wire rod is 10.0~15.0mm, the tensile strength is 1360~1410MPa, and the cross-sectional reduction rate is 45%~50%. The wire rod has high tensile strength, especially significantly improved plasticity, which can meet the 1960MPa bridge cable strength grade requirement while helping to reduce the crack tendency and torsional cracking risk under high area reduction rate.

[0039] Compared with the prior art, the beneficial effects of the present invention are at least:

[0040] (1) In view of the current manufacturing method of 1960MPa grade hot-rolled wire rod for bridge cables, the strengthening effect is weakened due to the limited and uncontrollable cooling phase transformation process, resulting in the formation of abnormal structures such as network carbon and martensite and insufficient plasticity. The manufacturing method of the present invention adopts C-Si-Mn-Cr hypereutectoid composition design combined with online molten salt strong isothermal technology. After spinning, it is first subjected to a front-stage molten salt treatment to control the wire rod to quickly skip the network carbide precipitation zone from the high-temperature austenite state to the troostite phase zone, thereby promoting the partial austenite structure to the fine layer layer. The troostite transformation of the spacing is then carried out through the subsequent molten salt heating isothermal short-time tempering to control the rapid transformation of the untransformed high-temperature austenite into pearlite, reduce the proportion of ferrite, increase the matrix strength, and provide more thermal power to promote the wire rod structure to be tempered at high temperature for a short time under isothermal conditions, which can reduce the organizational stress and dislocation density, and improve the plasticity of the wire rod. Finally, the roller is used for slow cooling to promote further toughening of the wire rod structure and improve the softening effect of the wire rod, so that the strength and plasticity of the hot-rolled wire rod are matched. At the same time, the production rhythm is faster than that of offline salt bath production, and it has good industrial adaptability.

[0041] (2) In view of the current situation that the hot-rolled wire rod for 1960MPa grade bridge cables has high C and hardenability elements, which brings the risk of wire breakage and torsion failure while meeting the strength grade, the hot-rolled wire rod of the present invention can simplify the component system and reduce the material cost. At the same time, the microstructure is mainly tempered troostite and tempered pearlite, containing a small amount of ferrite and quasi-spheroidized carbide, controlling abnormal structure and improving the uniformity of the structure. The matrix strength and plasticity are regulated by combining troostite and pearlite, reducing the proportion of ferrite in the structure, comprehensively improving the matrix strength, giving full play to the strengthening effect of C and alloy elements, and compensating for the strength loss caused by not adding alloy components such as Ni, B, and Mo. At the same time, the plasticity of the wire rod is significantly improved by tempering state regulation, and the strength-plasticity matching is achieved. The tensile strength can reach 1360~1410MPa and the cross-sectional shrinkage rate can reach 45%~50%. It can be used in the manufacture of 1960MPa grade bridge cables and other application fields. It can effectively reduce the risk of deep drawing wire making and torsion fracture while meeting the strength grade, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0043] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;

[0044] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;

[0045] Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION

[0046] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional reduction rate; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:

[0047] A preferred embodiment of the manufacturing method of the 1960MPa grade hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.86%, Si: 0.48%, Mn: 0.66%, Cr: 0.45%, P: 0.012%, S: 0.01%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt strong isothermal → roller slow cooling → coiling, specifically:

[0048] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote the uniform diffusion of carbon and alloy elements in the steel billet, and avoid decarburization of the steel billet. After the steel billet leaves the heating furnace, high-pressure dephosphorization water is used to remove the oxide scale on the surface of the steel billet, and then the steel billet is rolled into a wire with a diameter of 13mm through a rolling line. Appropriate rolling temperature, reduction amount and rolling speed are selected to control decarburization and dynamic recrystallization and grain refinement during the final rolling process. Specifically: the heating furnace is controlled to have a soaking temperature of 1145°C, and the furnace time is controlled to have a quenching temperature of 1000°C. The rolling speed is 32.5 m / s, the rolling time is 150 min, the air-fuel ratio is ≤0.5, the descaling pressure is 19 MPa, the initial rolling temperature is 1080 ° C, the final rolling temperature is 960 ° C, the final rolling reduction is 29%, and the rolling speed is 32.5 m / s; the spinning process is used to make the wire rod out of the rolling line into a wire rod through a spinning mechanism, and the wire rod is spread on the roller and transported along the roller. The wire rod is austenitized at an appropriate spinning temperature to prevent the precipitation of network carbides in the spinning stage, so as to form a large degree of supercooling later, thereby promoting the rapid nucleation of troostite with fine interlamellar spacing, and specifically: the spinning temperature is controlled to be 935 ° C.

[0049] The online molten salt strong isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 36°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase region, inhibiting the formation of network carbides, promoting the phase transformation of part of the austenite to form a sorbite structure with fine lamellar spacing as the main component, and improving the matrix strength. Then, it is conveyed by a roller through the second stage salt bath tank for rear-stage molten salt treatment, increasing the molten salt temperature and reducing the temperature. Low molten salt circulation rate promotes the transformation of untransformed high-temperature austenite to pearlite structure, performs short-time isothermal tempering, promotes tempering and softening of troostite and pearlite, transforms carbides to spheroidized structure, and improves the strength-plasticity matching of wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 516°C, the processing time is 20s, the molten salt circulation rate is 570t / h, and the molten salt temperature rise is ≤8°C; the molten salt temperature of the rear-stage molten salt is 582°C, the processing time is 150s, the molten salt circulation rate is 450t / h, and the molten salt temperature rise is ≤3°C.

[0050] The roller slow cooling process uses an open insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveyor roller into the insulation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 287°C at a slow cooling rate of 0.7°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 1 As shown, its microstructure is calculated by volume percentage as follows: 36% tempered troostite + 57% tempered pearlite + 2% ferrite + 5% quasi-spheroidized carbide, the lamellar spacing of tempered troostite is 115nm, the lamellar spacing of tempered pearlite is 170nm, the network carbide grade is 0, the mechanical property difference is 44MPa, the tensile strength is 1378MPa, and the section reduction rate is 48%.

[0051] Comparative Example 1:

[0052] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor air cooling, specifically: the heating furnace soaking temperature is controlled to be 1060°C, the furnace time is 210min, the initial rolling temperature is 1000°C, the final rolling temperature is 885°C, the rolling speed is 28m / s, and the spinning temperature is 860°C; the Stelmor strong air cooling adopts an air volume of 260,000 m per fan 3 / h, open 1~5# fans at 95%, cool the wire rod to 685℃ at a cooling rate of 9.2℃ / s, and then open 6~14# fans at 20%, cool the wire rod to 280℃ at a cooling rate of 3.2℃ / s. The hot-rolled wire rod is obtained after it comes off the line. Its microstructure is 87% troostite + 13% ferrite by volume, the network carbide grade is 3, the mechanical property difference is 81MPa, the tensile strength is 1330MPa, and the cross-sectional shrinkage rate is 32%.

[0053] From the comparison results of Example 1 and Comparative Example 1, it can be seen that compared with the C-Si-Mn-Cr hypereutectoid composition system, the Stelmor air cooling process is used, and the air cooling capacity is limited and uncontrollable, causing strength loss. While the strength grade is improved as much as possible, the plasticity and organizational uniformity are significantly reduced, bringing about the risk of wire breakage and torsion failure in wire making. The present invention is combined with the online molten salt strong isothermal technology. After spinning, it is first subjected to the front-end molten salt treatment to control the wire rod to quickly pass through the network carbide precipitation interval from the high-temperature austenite state and enter the troostite phase region, which can effectively control the network carbide and troostite phase transformation, and then the untransformed high-temperature austenite is quickly transformed into pearlite through the rear-stage molten salt heating to reduce the ferrite ratio. It can not only improve the matrix strength, but also reduce the organizational stress and dislocation density through short-time isothermal tempering, improve the plasticity of the wire rod, and can effectively reduce the subsequent deep drawing wire making and torsional fracture risks while meeting the strength grade.

[0054] Comparative Example 2:

[0055] A method for manufacturing a hot-rolled wire rod, which differs from Example 1 in that: the heating furnace soaking temperature is controlled to be 1080°C, the furnace time is 200min, the initial rolling temperature is 1010°C, the final rolling temperature is 900°C, the rolling speed is 29m / s, the spinning temperature is 885°C, and during the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 30°C / s, and the hot-rolled wire rod finished product is obtained after it is off the line. Embodiment 2:

[0056] A preferred embodiment of the manufacturing method of the 1960MPa grade hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.89%, Si: 0.55%, Mn: 0.53%, Cr: 0.35%, P: 0.012%, S: 0.01%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt strong isothermal → roller slow cooling → coiling, specifically:

[0057] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote the uniform diffusion of carbon and alloy elements in the steel billet, and avoid decarburization of the steel billet. After the steel billet leaves the heating furnace, high-pressure dephosphorization water is used to remove the oxide scale on the surface of the steel billet, and then the steel billet is rolled into a wire with a diameter of 10mm through a rolling line. Appropriate rolling temperature, reduction and rolling speed are selected to control decarburization and dynamic recrystallization and grain refinement during the final rolling process. Specifically: the heating furnace is controlled to have a soaking temperature of 1160°C, and the furnace time is 100°C. The time is 130min, the air-fuel ratio is ≤0.5, the descaling pressure is 20MPa, the initial rolling temperature is 1090℃, the final rolling temperature is 980℃, the final rolling reduction is 33%, and the rolling speed is 33m / s; the wire-spinning process is used to make the wire rod out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. An appropriate wire-spinning temperature is selected to austenitize the wire rod to prevent the precipitation of network carbides in the wire-spinning stage, so as to form a large degree of supercooling later, thereby promoting the rapid nucleation of sorbite with fine interlamellar spacing, and specifically: the wire-spinning temperature is controlled to be 950℃.

[0058] The online molten salt strong isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 36°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase region, inhibiting the formation of network carbides, promoting the phase transformation of part of the austenite to form a sorbite structure with fine lamellar spacing as the main component, and improving the matrix strength. Then, it is conveyed by a roller through the second stage salt bath tank for rear-stage molten salt treatment, increasing the molten salt temperature and reducing the temperature. Low molten salt circulation rate promotes the transformation of untransformed high-temperature austenite to pearlite structure, performs short-time isothermal tempering, promotes tempering and softening of troostite and pearlite, transforms carbides to spheroidized structure, and improves the strength-plasticity matching of wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 575°C, the processing time is 15s, the molten salt circulation rate is 550t / h, and the molten salt temperature rise is ≤8°C; the molten salt temperature of the rear-stage molten salt is 595°C, the processing time is 95s, the molten salt circulation rate is 360t / h, and the molten salt temperature rise is ≤3°C.

[0059] The roller slow cooling process uses an open insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveyor roller into the insulation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 275°C at a slow cooling rate of 0.9°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.

[0060] Comparative Example 3:

[0061] A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that: during the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 40°C / s, the molten salt temperature of the front-stage molten salt is 528°C, the treatment time is 32s, and the hot-rolled wire rod finished product is obtained after going offline.

[0062] Comparative Example 4:

[0063] A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that: during the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 33°C / s, the molten salt temperature of the front-stage molten salt is 585°C, the treatment time is 10s, and the hot-rolled wire rod finished product is obtained after going offline. Embodiment 3:

[0064] A preferred embodiment of the manufacturing method of the 1960MPa grade hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.9%, Si: 0.61%, Mn: 0.5%, Cr: 0.41%, P: 0.014%, S: 0.015%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt strong isothermal → roller slow cooling → coiling, specifically:

[0065] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote the uniform diffusion of carbon and alloy elements in the steel billet, and avoid decarburization of the steel billet. After the steel billet leaves the heating furnace, high-pressure dephosphorization water is used to remove the oxide scale on the surface of the steel billet, and then the steel billet is rolled into a wire with a diameter of 12mm through a rolling line. Appropriate rolling temperature, reduction amount and rolling speed are selected to control decarburization and dynamic recrystallization and grain refinement during the final rolling process. Specifically: the heating furnace is controlled to have a soaking temperature of 1135°C, and the furnace time is controlled to have a quenching temperature of 100°C. The rolling speed is 32.5 m / s, the rolling time is 170 min, the air-fuel ratio is ≤0.51, the descaling pressure is 19 MPa, the initial rolling temperature is 1065 ° C, the final rolling temperature is 950 ° C, the final rolling reduction is 31%, and the rolling speed is 32.5 m / s; the spinning process is used to make the wire rod out of the rolling line into a wire rod through a spinning mechanism, and the wire rod is spread on the roller and transported along the roller. The wire rod is austenitized at an appropriate spinning temperature to prevent the precipitation of network carbides in the spinning stage, so as to form a large degree of supercooling later, thereby promoting the rapid nucleation of troostite with fine interlayer spacing, and specifically: the spinning temperature is controlled to be 932 ° C.

[0066] The online molten salt strong isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 38°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase region, inhibiting the formation of network carbides, promoting the phase transformation of part of the austenite to form a sorbite structure with fine lamellar spacing as the main component, and improving the matrix strength. Then, it is conveyed by a roller through the second stage salt bath tank for rear-stage molten salt treatment, increasing the molten salt temperature and reducing the temperature. Low molten salt circulation rate promotes the transformation of untransformed high-temperature austenite to pearlite structure, performs short-time isothermal tempering, promotes tempering and softening of troostite and pearlite, transforms carbides to spheroidized structure, and improves the strength-plasticity matching of wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 548°C, the processing time is 24s, the molten salt circulation rate is 650t / h, and the molten salt temperature rise is ≤8°C; the molten salt temperature of the rear-stage molten salt is 570°C, the processing time is 135s, the molten salt circulation rate is 320t / h, and the molten salt temperature rise is ≤3°C.

[0067] The roller slow cooling process adopts an open insulation cover, and the wire rod passing through the second salt bath tank is transported by the conveyor roller into the insulation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 292°C at a slow cooling rate of 0.65°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.

[0068] Comparative Example 5:

[0069] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the molten salt temperature of the rear-stage molten salt is 556° C., the processing time is 45 seconds, and a hot-rolled wire rod finished product is obtained after the production line is off the line.

[0070] Comparative Example 6:

[0071] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the molten salt temperature of the rear-stage molten salt is 600° C., the processing time is 175 s, and a hot-rolled wire rod finished product is obtained after the production line is off. Embodiment 4:

[0072] A preferred embodiment of the manufacturing method of the 1960MPa grade hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.86%, Si: 0.65%, Mn: 0.7%, Cr: 0.4%, P: 0.015%, S: 0.013%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt strong isothermal → roller slow cooling → coiling, specifically:

[0073] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote the uniform diffusion of carbon and alloy elements in the steel billet, and avoid decarburization of the steel billet. After the steel billet leaves the heating furnace, high-pressure dephosphorization water is used to remove the oxide scale on the surface of the steel billet, and then the steel billet is rolled into a wire with a diameter of 15mm through a rolling line. Appropriate rolling temperature, reduction and rolling speed are selected to control decarburization and dynamic recrystallization and grain refinement during the final rolling process. Specifically: the heating furnace is controlled to have a soaking temperature of 1120°C, and the furnace time is 150°C. The time is 190min, the air-fuel ratio is ≤0.52, the descaling pressure is 18MPa, the initial rolling temperature is 1050℃, the final rolling temperature is 940℃, the final rolling reduction is 28%, and the rolling speed is 32m / s; the wire-spinning process is used to make the wire rod out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. An appropriate wire-spinning temperature is selected to austenitize the wire rod to prevent the precipitation of network carbides in the wire-spinning stage, so as to form a large degree of supercooling later, thereby promoting the rapid nucleation of troostite with fine interlamellar spacing, and specifically: the wire-spinning temperature is controlled to be 925℃.

[0074] The online molten salt strong isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 37°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase region, inhibiting the formation of network carbides, promoting the phase transformation of part of the austenite to form a sorbite structure with fine lamellar spacing as the main component, and improving the matrix strength. Then, it is conveyed by a roller through the second stage salt bath tank for rear-stage molten salt treatment, increasing the molten salt temperature and reducing the temperature. Low molten salt circulation rate promotes the transformation of untransformed high-temperature austenite to pearlite structure, performs short-time isothermal tempering, promotes tempering and softening of troostite and pearlite, transforms carbides to spheroidized structure, and improves the strength-plasticity matching of wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 545°C, the processing time is 30s, the molten salt circulation rate is 630t / h, and the molten salt temperature rise is ≤8°C; the molten salt temperature of the rear-stage molten salt is 558°C, the processing time is 50s, the molten salt circulation rate is 300t / h, and the molten salt temperature rise is ≤3°C.

[0075] The roller slow cooling process uses an open insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveying roller into the insulation cover, which promotes further toughening of the wire rod structure and improves the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 296°C at a slow cooling rate of 0.5°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.

[0076] Comparative Example 6:

[0077] A method for manufacturing a hot-rolled wire rod, which differs from Example 4 in that: the method is manufactured according to a process flow of rolling → spinning → online molten salt strong isothermal → air cooling, wherein the air cooling is performed by opening a heat preservation cover, conveying the wire rod through a second salt bath tank by a conveyor roller, and controlling the wire rod to be cooled to 290°C at a slow cooling rate of 1.9°C / s; and obtaining a finished hot-rolled wire rod after it comes off the line.

[0078] The hot rolled wire rods obtained in the above examples 1 to 4 and comparative examples 2 to 7 were subjected to microstructure and performance testing, and the comparative results obtained are shown in Table 1 below:

[0079] Table 1. Comparison of microstructure and performance of hot rolled wire rods with different compositions and manufacturing methods

[0080]

[0081] It can be seen from the results of Examples 1 to 4 that the microstructure of the hot-rolled wire rod of the present invention is mainly composed of tempered troostite and tempered pearlite, containing a small amount of ferrite and quasi-spheroidized carbides, which fully exert the strengthening effect of C and alloy elements, and at the same time significantly improve the plasticity of the wire rod through tempering state regulation, and can achieve a tensile strength of 1360~1410MPa and a cross-sectional reduction rate of 45%~50%. It can be used in the manufacture of 1960MPa-level bridge cables and other application fields, which is beneficial to improve the drawing yield and torsion qualification rate while meeting the strength grade of the bridge cables.

[0082] From the comparison results of Example 1 and Comparative Example 2, it can be seen that by selecting a higher spinning temperature to austenitize the wire rod structure, it is possible to avoid the formation of network carbides due to too low a temperature during the spinning stage, and to provide favorable conditions for the subsequent formation of a larger temperature gradient to inhibit the precipitation of network carbides and promote the nucleation of troostite.

[0083] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the lower the molten salt temperature of the front-stage molten salt and the longer the treatment time, the more the high-temperature austenite phase troostite structure is transformed, the finer the troostite lamellar structure is, and the matrix strength increases. However, if the molten salt temperature is too low and the treatment time is too long, more troostite nuclei will be formed, which will affect the transformation of pearlite structure and reduce the plasticity of the matrix.

[0084] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the higher the molten salt temperature of the front-stage molten salt and the shorter the treatment time, the more unfavorable it is for the nucleation of troostite with mainly fine lamellar spacing, which increases the untransformed high-temperature austenite structure, increases the pearlite transformation, and reduces the matrix strength. However, if the molten salt temperature is too high and the treatment time is too short, the troostite transformation is too little, which will affect the wire rod strength and drawing hardening performance, and will also reduce the cooling rate of the wire rod, affect the control of the network carbide, and cause increased mechanical fluctuations.

[0085] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the lower the molten salt temperature of the latter stage molten salt is, the more conducive it is to refining the pearlite lamellar spacing and improving the matrix strength and drawing performance. The shorter the treatment time is, the lower the tempering softening effect and the plasticity of the wire rod are. However, if the molten salt temperature is too low and the treatment time is too short, it is difficult to provide more thermal power for tissue softening and carbide spheroidization, which will make the wire rod insufficiently plastic.

[0086] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the higher the molten salt temperature of the latter molten salt and the longer the treatment time, the more the untransformed austenite structure is transformed into the pearlite structure, and at the same time, more thermal power can be provided to promote short-time isothermal tempering of troostite and pearlite structure, promote carbide spheroidization, and improve matrix plasticity. However, if the molten salt temperature is too high and the treatment time is too long, there is a risk of softening too quickly, losing wire rod strength due to excessive softening, and losing strength and plasticity due to aggregation and growth of carbides such as Cr.

[0087] From the comparison results of Example 4 and Comparative Example 7, it can be seen that the use of roller slow cooling can avoid the loss of plasticity of the wire rod caused by too high cooling rate of the wire rod, continue the tempering effect of the later stage of the molten salt treatment, promote further toughening of the structure, and improve the softening effect.

[0088] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for manufacturing a 1960MPa grade hot-rolled wire rod for bridge cables, characterized in that: The manufacturing method thereof comprises: The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, and the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.86%~0.90%, Si: 0.48%~0.65%, Mn: 0.50%~0.70%, Cr: 0.35%~0.45%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥925°C, it is subjected to an online molten salt strong isothermal treatment, so that the wire rod first passes through the front-stage molten salt and is cooled at a cooling rate of ≥36°C / s, and enters the Soxhlet state from the austenite state. The bulk phase zone promotes the transformation of part of austenite to troostite, and then undergoes isothermal treatment with molten salt in the latter stage to promote pearlite phase transformation and isothermal tempering, and finally undergoes slow cooling on a roller to produce a hot-rolled wire rod with a microstructure including 33% to 40% tempered troostite and 53% to 62% tempered pearlite by volume, and the rest being a mixed structure of ferrite and quasi-spheroidized carbide; the molten salt temperature of the former stage is 545 to 575°C, and the treatment time is 15 to 30s; the molten salt temperature of the latter stage is 558 to 595°C, and the treatment time is 50 to 150s.

2. The method for manufacturing the 1960MPa grade hot rolled wire rod for bridge cables according to claim 1, characterized in that: Before the rolling, the soaking temperature of the heating furnace is controlled to be 1120-1160° C., the time in the furnace is 130-190 min, the air-fuel ratio is ≤0.52, and the descaling pressure is ≥18 MPa.

3. The method for manufacturing the 1960MPa grade hot rolled wire rod for bridge cables according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1050-1090° C., the final rolling temperature is controlled to be 940-980° C., and the final rolling reduction is controlled to be 28%-33%.

4. The method for manufacturing the 1960MPa grade hot rolled wire rod for bridge cables according to claim 3, characterized in that: During the rolling, the rolling speed is controlled to be ≥32 m / s.

5. The method for manufacturing 1960MPa grade hot rolled wire rod for bridge cables according to claim 1, characterized in that: The molten salt circulation volume of the front-stage molten salt is 550-650 t / h, and the molten salt temperature rise is ≤8°C; the molten salt circulation volume of the rear-stage molten salt is 300-450 t / h, and the molten salt temperature rise is ≤3°C.

6. The method for manufacturing 1960MPa grade hot rolled wire rod for bridge cables according to claim 1, characterized in that: The roller slow cooling controls the wire rod to be cooled to below 300° C. at a slow cooling rate of 0.5-0.9° C. / s for coiling.

7. A 1960MPa grade hot rolled wire rod for bridge cables, characterized in that: The hot-rolled wire rod is manufactured by the method for manufacturing 1960MPa grade hot-rolled wire rod for bridge cables as described in any one of claims 1 to 6.

8. The 1960MPa grade hot rolled wire rod for bridge cables according to claim 7, characterized in that: The interlamellar spacing of the tempered bainite is 80-135 nm, the interlamellar spacing of the tempered pearlite is 155-180 nm, the network carbide grade of the hot-rolled wire rod is grade 0, and the mechanical property difference is ≤45 MPa.

9. The 1960MPa grade hot rolled wire rod for bridge cables according to claim 7, characterized in that: The hot-rolled wire rod has a diameter of 10.0-15.0 mm, a tensile strength of 1360-1410 MPa, and a cross-sectional shrinkage of 45%-50%.

Citation Information

Patent Citations

  • A low-alloy steel and a high-strength, high-ductility wire rod made therefrom for wire processing.

    CN109554631B

  • 15.9-grade annealing-free hot-rolled high-carbon vanadium-containing cold heading steel wire rod and manufacturing method thereof

    CN118639123A

  • Cord steel wire rod suitable for deep drawing and manufacturing method therefor

    WO2023056658A1